Computed tomographic analysis of medial clavicular epiphyseal fusion for age estimation in Indian population. (September 2020) - Shedge, Rutwik; Kanchan, Tanuj; Garg, Pawan Kumar; Dixit, Shilpi Gupta; Warrier, Varsha; Khera, Pushpinder; Krishan, Kewal
Highlights: Age estimation is a crucial medicolegal aspect in civil and criminal law. Medial clavicular epiphyseal (MCE) fusion is a reliable method for age estimation. Computed Tomography is a newer foray into the science of Forensic age estimation. CT of the MCE will allow assessment of whether an individual has reached the age of majority. Abstract: Forensic age estimation is a crucial aspect of the identification process. While epiphyseal fusion of long bones has been studied for age estimation since a long time, over the past few years, the role of medial clavicular epiphyseal fusion in age estimation is being explored. The medial clavicular epiphyseal fusion can be used to estimate age in young adults, and can also determine whether medicolegally significant ages of 16 and 18 years have been attained by an individual. The present study aimed at generating regression models to estimate age by evaluating the medial clavicular epiphyseal fusion in Indian population using Schmeling et al. and Kellinghaus et al. method, and to assess whether an individual's age is over medicolegally significant thresholds of 16 and 18 years. Degree of ossification of the medial clavicular epiphysis was studied in CT images of 350 individuals aged 10.01–35.47 years. Significant statistical correlation (P < 0.001) was observed between the degree of fusion and the chronological age of the participants, with Spearman's correlation (ρ) = 0.918 in females, and ρ = 0.905 in males. Regression models were generated using degree of ossification of medial end of clavicle of 350 individuals (147 females and 203 males) and these models were applied on a test set of 50 individuals (25 females and 25 males). Mean absolute error of 1.50 for females, 1.14 for males, and 1.32 for the total test set was observed when the variance between the chronological ages and estimated ages was calculated.